3381 Reducing Problem Records in the Johns Hopkins University ClinicalTrials.gov Protocol Registration and Results System (PRS). (27th March 2019) - Tetteh, Oswald; Lalji, Aliya; Nuamah, Prince Samuel; Keyes, Anthony
Abstract : OBJECTIVES/SPECIFIC AIMS: The Johns Hopkins University Clinicaltrials.gov (CT.gov) Program has previously reported on a study showing reduction of "Late Results – per FDAAA" from 111 to 0. What we hope to do here is to focus on non-late results records. Over the years, some institutions spend their efforts solely on late results in order to avoid any penalties from the Food and Drug Administration (FDA). However, there are a number of variables that labels "problem records" within the Protocol and Registration System (PRS). These records are also subject to penalties. Our goal has been to minimize problem records and establish processes to improve and maintain our institutional compliance in regards to regulations governing clinical trials registration and results reporting. METHODS/STUDY POPULATION: The Johns Hopkins University implemented a Clinicaltrials.gov program solely mandated to assist Principal Investigators (PIs) and other study team members with clinical trial registration and results reporting. The program has developed processes in its duty towards reducing problem records in the PRS. Full-time staff have been assigned to assist research teams with registration and results reporting, while ensuring compliance with all relevant regulations. Several methods have been utilized to track metrics, such as monthly reports and internal databases. Features within the PRS have also been used to draw attention to newly-identified problem records on a daily basis in order to rectify these issues with the study team promptly. In order to ensure compliance, our office communicates with study teams regarding the problems within their CT.gov record that requires attention. In challenging cases, our program will also collaborate with the CT.gov PRS Team at the NIH to facilitate the process and avoid multiple review cycles, which can delay registration or the posting of results. Our Program has also formed internal collaborations with the Institutional Review Board (IRB) which allows us to verify study status and view active study team members. This is especially useful in cases where the study team members who are listed on the CT.gov record cannot be reached or the contact information is outdated (a common occurrence with older studies). With access in the IRB, we can contact the current study team members who may not be listed in CT.gov and assist them to resolve any outstanding issues of non-compliance within their CT.gov record. RESULTS/ANTICIPATED RESULTS: From September 2015 (before our program was established) to September 2016 (three months after the institution of our program), the total amount of problem records increased from 44% (339/774) to 45% (383/852). Since then, the processes we have developed resulted in a decline in problem records to 30% (282/955) in September 2017, and a further decline to 8% (83/1075) as of September 2018. The short rise that was observed in 2016, was a potential indicator that if our program was not instituted, it would have been more difficult to maintain compliance. DISCUSSION/SIGNIFICANCE OF IMPACT: According to the FDA Draft Guidance released in September 2018 referring to the Civil Money Penalties Relating to the ClinicalTrials.gov Data Bank, there are a number of ways to violate the FDA regulations, resulting in potential monetary penalties, which include "failing to submit required clinical trial information or submitting clinical trial information that is false or misleading". These regulations apply to results as well as registration and study status updates. By paying attention to all problems that are identified by the PRS, institutions can rectify errors and remain complaint with all regulations that govern clinical trial registration and results reporting.